Exploring Emerging Translanguaging Practices among International Undergraduates in EAP Courses in South Korea - Jang, Jinsil (Forum for Linguistic Studies, 2025)
As the number of international students in South Korean universities increases, top-tiered institutions are gradually adopting English-Medium Instruction (EMI) policies without considering the linguistic diversity of these students (Lee & Lee, 2018). Similarly, my English for Academic Purposes (EAP) courses were initially designed to be solely conducted in English, assuming that it would be the most effective medium of instruction. However, this English-only approach created tensions between academic and local language practices, which affected language use in my classes. These tensions mainly arise from the differences between students’ local language practices and the language used in academia, making it challenging for EAP instructors to design courses that cater to both Korean and international students. To address these gaps, this autoethnographic case study draws on the frameworks of EAP, translanguaging, and action research. The study explores the challenges faced in EAP classes at a regional Korean university and how a bilingual Korean-English instructor addressed them. Throughout one semester in 2022, I conducted action research and redesigned my EAP course to create a translanguaging space for multilingual students. The findings revealed that English-only practices hindered students’ ability to fluidly switch between languages, limiting their proficiency in using English for everyday and academic communication (Canagarajah, 2011). Monolingual values embedded in EAP courses also hindered meaningful communication among students with different language backgrounds. To address these challenges, a transition from English-only to multilingual practices was necessary in EAP courses, requiring the development of pedagogical approaches that activate students’ multilingual resources in English as a Foreign Language (EFL) contexts. This study suggests the need for more action research in EAP and EFL settings to improve classroom teaching practices and enhance students’ learning experiences (Efron & Ravid, 2019).